The Impact of Covid-19 Pandemic on Women: A Case Study of Northern Division Kabale Municipality Kabale District. - Ankunda, Tomson (Kabale University, 2024)
The study sought to examine the impact of COVID-19 on women Northern Division, Kabale Municipality Kabale District- Uganda. The study objectives were; to find out the causes of gender based violence in homesteads, to establish the impact of Covid 19 on women, and to find out the solutions to gender-based violence in homesteads. The study largely applied qualitative research design. To a lesser extent, it also applied quantitative research design where descriptive statistics were used. According to the study findings, it was found out gender violence is a major cause of low household incomes in most homesteads for instance beating of women, and denying women the rights to access education, land, and property which often undermines their income earnings hence leading to low household incomes in most homesteads. However, apart from gender-based violence, other several factors contribute to low household incomes such as Political stability, and natural calamities. The study concludes that individual-level causes are biological and personal history causes that increase the risk of violence. For example, a low level of education, young age ( early marriage), and low economic status/income have been associated as risk causes for both experiencing and perpetrating intimate partner violence. The study recommends that the government needs to ensure that they are held accountable for the violence that they commit, including violence against women and girls. The government should put in place initiatives targeting the engagement of men to overcome violence against women. This is because they need to be adequately supported with human and financial resources, but without reducing resources from women's programs.